Ensaios sobre pobreza, desigualdade de renda e crescimento econômico no Brasil - Silva, Janaina Cabral da (2015)
This dissertation is composed by 3 papers which, where each paper is a dissertation chapter. This first chapter entitled “Relationship between wealth inequality and economic growth in Brazil” analyses the relationship from Kuznets inverted U hypothesis from 1995 to 2012. The inverted U supposition – Kuznets hypothesis (1955) – deals, in short term, exists a positive connection among wealth inequality and the per capita income level. In the long term, we observe a inverted U relationship, because there is a inversion of this relation. Thus, we use dynamic panel model and the Generalized method of moments system estimation method, developed by Arellano-Bond (1991), Arellano-Bover(1995) and Blundell e Bond (1998). The results show that the Kuznets hypothesis was confirmed. Based in the theories which seek relates poverty, inequality, economic growth and welfare, the chapter two aims to decompose the poverty variation, basing in the following factors: trend effect, growth effect, inequality effect and residual effect, for Brazilian states between 2001 and 2012. To reach this objective, we estimated a statistic model with panel data, using poverty variables, per capita familiar income and gini coefficient, extracted from PNAD. The results estimated allow to infer which in the most of Brazilian states, the growth effect stood out in relation to another effects regarding the explanation of poverty reduction in the period analyzed. Nonetheless, the distribution effect too had its importance in this process, followed by trend effect. However, the residual effect had low explanation power. Thus, finishing this dissertation, the chapter three analyses the poverty time for Brazil, using indicators as ratio of poor in time ( ), the time poverty gap, which measures its intensity ( ) and the squared poverty time, who measures its severity ( ). Then, from estimation of statistical model with panel data, using the variables “all labor income”, “age”, average years of study to explain the poverty time in the Brazilian states. The results indicate the a increase in the income have been occurring, reducing the poverty in time; how much higher is the individual age, higher the chance of they being poverty in time; and, higher education level of people, greater their privation of time in comparison to people with lower education level.